O sujeito teuto-brasileiro e o (des)uso do dialeto alemão em Chapada - Knob, Glaucia (2018)
The topic of the research entitled The German-Brazilian subject and the use (or disuse) of the German dialect in the city of Chapada is limited to the understanding of the application of theGerman dialect in the community of Chapada, RS, Brazil. This study aimed to understand the path of disuse of the German dialect in the city, identifying the main factors that have triggered and are still causing such phenomenon. The corpus of analysis includes discursive fragments from the transcription of semi-structured interviews with the possibility of open questions, performed with fifteen descendants of German immigrants from the city of Chapada divided into three age groups (20 to 40, 40 to 60, and 60 and over). The theoretical and methodological support for the discourse analysis was the Discursive Semiotic Theory, focusing on the discourse level in order to identify the topics presented in the speech of these descendants and relating them to the culture studies that discuss cultural and identity formation. To address the history of German immigration in Brazil and in the state of Rio Grande do Sul, particularly in the city of Chapada, the theoretical references of the geographical space of the study, as well as of the concepts of culture, identity, language, and social and economic power are based on Bueno (2006, 2011), Fausel (1961), Gnerre (2009), Gregory (2013), Hall (2006, 2011), Neumann (2009, 2014), Silva (2011), Steffen (1984), and Woodward (2011). The Discursive Semiotic Theory was addressed on the basis of Greimas (1975, 1979), Discini (2005, 2007a, 2007b), Barros (2011, 2012, 2014), and Fiorin (2002, 2010, 2012, 2016). Regarding the objectives, the study is descriptive and explanatory; as for the procedures, it is bibliographic and a case study, in which data (discourses) were collected through interviews with the subjects. The study is also classified as qualitative regarding the problem approach. The significance justification of this study refers to the contribution to clarify relevant aspects of the use (or disuse) of the German language in Chapada, considering the community is German-based, and to contribute with linguistic theories. The analysis of discourse fragments showed that, historically, government decisions have influenced and interfered with social institutions (school and family) by prohibiting the use of the German language. Consequently, families reduced the use of the language, schools stopped teaching German and started teaching English instead, and there was prejudice toward people with traits that might identify them as German-Brazilians.